PRODUCTION-ECONOMIC FEATURES OF FRUIT PROCESSING - Lukač Bulatović, Mirjana (Economics of Agriculture, 2010)
On average, in the period 1980-2007, the biggest fruit product production volume was that of fruit juices (78,661 t) and frozen fruit (22,223 t). These products make 81.5% of the total production of analysed products in Serbia. With an average annual production of 34,203 t, Vojvodina accounts for 27.6% of the total production. With an exception of fruit juice production, i.e. forzen fruit, production of other analysed fruit products is in decline. The most pronounced decline in production volume is found with dried fruit (rate of change: -16.77%) and compote (rate of change: -14.71% ). In 2007, production of fruit products in the analysed processing facility was cost-effective. A positive financial result is particularly evident per unit of product (33.26 din/kg), i. e. a high degree in cost-effectiveness in jam production (1.29). Cost-effectiveness of the analysed product was, on average, 21.63%, ranging between 14.57% (fruit juice production) and 28.59% (jam production).